Pengalaman Supportive Environtment Dalam Tiap Tahap Recovery Survivor Skizofrenia di Kalimantan Barat - Hidayah, Nurul; Rahmawati, Nadia; Nisma, Nisma (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The treatment of mental disorders in Indonesia currently still relies on the principle of cure alone as the main therapy. In fact, the causes of mental disorders are multicomplex and do not stand alone, starting from genetic factors, birth conditions, brain injury, trauma, social pressure, and stress can cause mental disorders. Therefore, there is a need for a solution to overcome this disease by empowering patients, through a recovery process with support from those closest to them (supportive environment). Supportive environments have an important role in mental disorders, whether they are the cause of mental disorders or the process of treating and healing individuals or family members who experience mental disorders. The recovery process that patients undergo is not just to recover from illness, but to make the lives of people who experience limitations due to their illness more meaningful. Recovery emphasizes that although individuals cannot control the symptoms of their illness, they can control their lives. This research is to explore the life experiences of supportive environment components in each stage of recovery of schizophrenia survivors in West Kalimantan. This research design uses descriptive qualitative with a descriptive phenomenological approach. The population in the research is the supportive environment component. The number of participants was determined using a purposive sampling technique, namely 6 participants consisting of 4 families who cared for schizophrenia survivors and 2 nurses in charge of social welfare programs at the Community Health Center. Supportive environment experiences were explored through in-depth interviews and data analysis using the Colaizzi method. 3 themes were obtained from the research, namely: 1) Economic and psychological burden on families as caregivers, 2) Lack of knowledge of nurses in carrying out early detection of mental health and 3) Lack of completeness of supporting human health services at Community Health Centers. Keywords: Recovery, Supportive Environment, Schizophrenia Survivor  ABSTRAK Penanganan gangguan jiwa yang ada di Indonesia saat ini masih mengandalkan prinsip cure  saja sebagai terapi utama. Padahal, penyebab gangguan jiwa itu multikompleks tidak berdiri sendiri mulai dari faktor genetis, kondisi para-kelahiran, cedera otak, trauma, tekanan sosial, hingga stres bisa menyebabkan gangguan mental. Oleh sebab itu perlu adanya solusi untuk mengatasi penyakit tersebut dengan cara melakukan pemberdayaan pada pasien, melalui sebuah proses recovery dengan dukungan dari orang terdekat (supportive environtment). Supportive environtment memiliki peranan penting terhadap gangguan jiwa entah menjadi penyebab dari gangguan jiwa ataupun proses pengobatan dan penyembuhan individu atau anggota keluarga yang mengalami gangguan jiwa. Proses recovery yang dijalani pasien bukan hanya untuk sekadar pulih dari penyakit, tapi untuk membuat kehidupan orang yang mengalami keterbatasan akibat penyakitnya menjadi lebih berarti. Recovery menekankan bahwa meskipun individu tidak bisa mengontrol gejala penyakitnya tapi mereka bisa mengontrol kehidupan mereka. Penelitian ini yaitu untuk mengeksplorasi pengalaman hidup komponen supportive environtment dalam tiap tahap recovery survivor skizofrenia di Kalimantan Barat. Rancangan penelitian ini menggunakan deskriptif kualitatif dengan pendekatan fenomenologi deskriptif. Populasi dalam penelitian yaitu komponen supportive environtment. Jumlah partisipan ditentukan  melalui teknik purposive sampling yakni 6 partisipan yang terdiri dari 4 orang keluarga yang merawat survivor skizofrenia  dan 2 orang perawat penanggung jawab program keswa di Puskesmas. Pengalaman supportive environtment digali melalui wawancara mendalam dan analisa data menggunakan metode Colaizzi. Penelitian diperoleh 3 tema yaitu : 1) Beban ekonomi dan psikologis keluarga sebagai caregiver, 2) Kurangnya pengetahuan perawat dalam melakukan deteksi dini Kesehatan jiwa dan 3) Kurangnya kelengkapan penunjang pelayanan keswa di Puskesmas. Kata Kunci: Recovery, Supportive Environtment, Survivor Skizofrenia